Spousal Care and Pain Among the Population Aged 65 Years and Older: A European Analysis - Barbosa, Fátima; Delerue Matos, Alice; Voss, Gina; Costa, Patrício (Frontiers in Medicine, 2021)
Background: Spousal care is the most important source of informal care in old age. Nevertheless, despite the growing importance of this issue, the association between providing spousal care inside the household and pain remains unexplored in Europe. Objective and Methods: This study aims to estimate the prevalence of pain reported by spouse caregivers aged 65 plus that provide care inside the household and to investigate the association between providing spousal care and pain. Data from 17 European countries that participated in wave 6 of the Survey of Health, Ageing and Retirement in Europe (SHARE) is used. The analyses are based on 26,301 respondents aged 65 years and older who provide informal care inside the household to their spouse/partner exclusively (N=1895) or do not provide any informal care (inside or outside the household) (24406). Descriptive statistics and multilevel logistic regressions (individual-level as level 1, and country as level 2) were performed. Results: Overall, spouse caregivers report pain more often (63.4%) than their non-caregiver`s counterparts (50.3%). Important differences in the prevalence of pain among spouse caregivers were found between countries, with Portugal (80.3%), Spain (74.6%), France (73%), Italy (72.4%) and Slovenia (72.1) showing the highest prevalence of pain, and Denmark (36%), Switzerland (41.5) and Sweden (42.3%), the lowest. Results from multilevel logistic regressions show that European individuals aged 65+ who provide spousal care have an increased likelihood of reporting pain (OR 1.30; CI =1.13 -1.48). Conclusion: Our results suggest that in Europe, spouse caregivers aged 65+ are at greater risk of experiencing pain. Therefore, European policymakers should consider spouse caregivers as a health priority group, and take measures to ensure they receive comprehensive health and socio-economic support.